Improved Outcome in Local Ewing Sarcoma With an Intensified Pilot Treatment Protocol SCMCIE 94. Issue 2 (March 2019) - Ash, Shifra; Yaniv, Isaac; Toledano, Helen; Stein, Jerry; Kollender, Yehuda; Fenig, Eyal; Konen, Osnat; Bar-Sever, Zvi; Issakov, Josephine; Avigad, Smadar; Cohen, Ian J.
Abstract : This study evaluated the effect of an intensified pilot protocol, SCMCIE 94, on the outcome of Ewing sarcoma (EWS). The cohort included 121 patients with local or metastatic EWS treated at a tertiary pediatric medical center with the SCMCIE 94 (protocol 3, 1994 to 2011) or an earlier protocol (protocol 2, 1988 to 1994; protocol 1, 1985 to 1988). All protocols included 4 to 6 courses of chemotherapy, radiation, and surgery. Clinical data were collected retrospectively by chart review. Survival rates for protocol 3 were as follows: all patients—5-year event-free survival (EFS): 52.5%±5.6%, 10-year EFS: 49.3%±5.8%, 5-year overall survival (OS): 68.8%±5.3%, and 10-year OS: 51.1%±6.3%; patients with localized disease (any site)—5-year EFS: 63.5%±6.0% and 5-year OS: 77.2%±5.3%; patients with localized extremity disease—5-year EFS: 78.95%±8.3%, 10-year EFS: 68.6%±10.0%, 5-year OS: 90.7%±6.2%, and 10-year OS: 71.1%±11.2%. Protocol 3 was associated with an increase in 10-year EFS of 16% overall and 33% in patients with localized extremity disease compared with protocols 1+2, and a significant improvement in 5-year EFS and OS in patients with any localized disease ( P =0.001). No survival benefit was found for metastatic disease. On multivariate analysis, protocol and metastatic disease were significantly independent prognostic factors. The intensified SCMCIE 94 protocol seems to increase survival in patients with localized but not metastatic EWS.